HUBUNGAN POLIMORFISME GEN PVULL RESEPTOR ESTROGEN ALPHA PADA KEJADIAN KARSINOMA OVARIUM EPITEL - OCTARIANA OCTARIANA (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2015)
The polimorfisms of estrogen receptor a gene induce proliferation of ovarian epithelial proliferation and antiapoptosis of the cell, this alteration may cause suspectibility to the occurrence of an ovarian carcinoma. Estrogen receptor a is located on chromosome 6q24-q27 and have 14 sites ofSNPs the most abserved SNP lies in intron 1 that can be recognized by pvull. The aim of this study to analyze association between polymorphism Pvull Estrogen Receptor a gene and the Occurance of Epithelial Ovarian Carcinoma at Dr. Muhammad Hoes in hospital Palembang. Case contras study using have been conducted at hospital Dr. Muhammad Hoesin Palembang 2011, thare were 60 sample recruited and devided into two groups, case were 3 0 people and control were 30 people, who have met the inclusion criteria, how studies with PCR techniques for genotyping and allotipe analysis were performed PCR-RFLP Statistic analysis with chi-square at a =0,05. These results obtained in the TT genotype of 16, 7%, TC by 50% and CC 33,3%. Allel Tthare are 41, 7% and allel C there are 58,3%. Results obtained for genotype analysis of the value of pvalue= 0, 748, ood ratio (OR)= 1,522,for allotype pvalue=0,201, OR= 1,711 which means Ho is received. The conclutions of this study there have association between polymorphism Pvull Estrogen Receptor a gene and Epithelial Ovarian Carcinoma at Dr. Muhammad Hoesin hospital Palembang (OR =1,522 and 1, 711) but the associantion in this study was no significant (p=O, 78 andp=0,201)